Evaluation of beef breeds for rangeland weaner production in Zimbabwe. 2. Productivity of crossbred cows and heterosis estimates - Tawonezvi, H.P.R.; Ward, H.K.; Trail, J.C.M.; Light, D.E. (Cambridge University Press, 1988)
Assesses reproductive performance, body weight & live weight, pre-weaning growth, and viability of progeny sired by various unrelated breeds which are representative of the Sanga X Sanga, Sanga X Zebu, Bos taurus X Sanga, Bos taurus X Zebu, and Bos taurus X Bos taurus crossbred groups. Measures the influence of sire breed on calf birth and weaning weight and viability to weaning. Estimates heterosis levels for the range of performance traits.